Optimum Green Synthesis of Silver Nanoparticles with the Highest Antibacterial Activity against Streptococcus mutans Biofilm. (19th September 2022) - Chahardoli, Azam; Safaei, Mohsen; Mobarakeh, Mohammad Salmani; Fallahnia, Nima; Fatehi, Behnam; Imani, Mohammad Moslem; Golshah, Amin
Abstract : Nowadays, resistance to antibiotics has developed in bacterial microorganisms related to dental and oral infections, leading to major problems in public health. Using nanoparticles, particularly silver nanoparticles (AgNPs) may offer a new strategy for the prevention and treatment of dental infections. In the current study, AgNPs were synthesized using Halomonas elongata at different conditions according to nine experiments designed by the Taguchi method, and their antibacterial effects were investigated on a Streptococcus mutans biofilm. The effects of three factors, including silver nitrate (AgNO3 ) concentration, incubation time, and temperature at three different levels, were studied to optimize the synthesis of AgNPs under the designed experiments. Then, the antibacterial effects of these NPs on the S. mutans biofilm were examined by the colony-forming unit (CFU) method. According to the results, green-synthesized AgNPs under optimal conditions properly inhibit the formation and growth of the S. mutans biofilm. Furthermore, different analyses were applied to investigate the formation, structural, and morphological properties of the green-synthesized AgNPs under optimum conditions. The obtained results of this study indicated that the green-synthesized AgNPs could be a promising antimicrobial agent in the dental and medicinal industry.